At-admission hyperglycemia is consistently associated with poor prognosis and early intervention can improve outcomes in patients with COVID-19. Issue 6 (November 2020) - Singh, Awadhesh Kumar; Singh, Ritu
Abstract: Background & Aims: At-admission hyperglycemia have been associated with poorer outcome during critical illnesses. At-admission hyperglycemia in previously unknown diabetes is not uncommonly encountered entity in patients with COVID-19. We sought to find out the outcomes of at-admission hyperglycemia and effect of early intervention to achieve optimal glycemic control in relation to COVID-19 patients. Methods: We searched the PubMed and Google Scholar database up till August 20, 2020 using specific keywords related to our aims and objectives. Results: All currently available evidences clearly hint that at-admission hyperglycemia in patients with COVID-19 is associated with a poorer outcome, compared with normoglycemic individuals. Fortunately, early intervention by achieving an optimal glycemic control has also been associated with a significant improvement in the outcomes in patients with COVID-19. Conclusion: At-admission hyperglycemia should be taken seriously by all clinicians treating patients with COVID-19. All efforts should be made towards an optimal glycemic control in patients with COVID-19, even in absence of pre-existing diabetes. Highlights: At-admission hyperglycemia is associated with poor outcomes in patients with COVID-19. Early intervention and optimal glycemic control improve the outcomes in patients with COVID-19. All efforts should be made to achieve reasonable glycemic control in patients with COVID-19.